2021
DOI: 10.1111/jcmm.16976
|View full text |Cite
|
Sign up to set email alerts
|

Role of HRTPT in kidney proximal epithelial cell regeneration: Integrative differential expression and pathway analyses using microarray and scRNA‐seq

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The previous study used HPT cells that showed a marked reduction in 21 lysosomal-and mTOR-related genes, which were used to compare the basal expression of these genes in the HRTPT and HREC24T cells. The HRTPT and HREC24T cells were compared using global gene expression to determine the differentially expressed genes between the two cell lines [11]. This comparison showed that only a few of the 35 lysosomal genes and 15 mTOR genes identified as being altered by elevated glucose concentrations present in either the HRPT or HREC24T cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous study used HPT cells that showed a marked reduction in 21 lysosomal-and mTOR-related genes, which were used to compare the basal expression of these genes in the HRTPT and HREC24T cells. The HRTPT and HREC24T cells were compared using global gene expression to determine the differentially expressed genes between the two cell lines [11]. This comparison showed that only a few of the 35 lysosomal genes and 15 mTOR genes identified as being altered by elevated glucose concentrations present in either the HRPT or HREC24T cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study on the HRTPT and HREC24T cells demonstrated only 873 differentially expressed genes between the HRTPT and HREC24T cell lines, narrowing the analysis of the number of genes potentially altered by nephrotoxic agents or conditions. Renal progenitor cells are difficult to study in the intact kidney due to their sparse population and scattered locations [11]. Thus, the present cell lines may help identify factors and mechanisms involved in renal repair in the intact kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, our laboratory identified an immortalized human renal proximal tubule epithelial cell line, RPTEC/TERT1, that also displays the two cell populations, one that cell sorting was used to isolate two new immortalized cell lines, one HRTPT that co-expresses PROM1 and CD24, and another, HRECT24T that expresses CD24 and no PROM1 [ 11 ]. The HRTPT cells expressed the features defined for RPCs while the HRECT24T cells displayed no features of RPCs [ 11 , 12 , 13 ]. The HRTPT cells provide a human cell culture model to determine if PROM1/CD24 co-expressing RPCs are susceptible to nephrotoxic agents.…”
Section: Introductionmentioning
confidence: 99%